6-Formyl-2-naphthyl cis-1,5,7-trimethyl-2,4-dioxo-3-azabicyclo[3.3.1]nonane-7-carboxylate - Xu, Sheng-guang (International Union of Crystallography, 2009)
In the title compound, C(23)H(23)NO(5), the C(5)N ring adopts an envelope conformation with a C atom as the flap, whilst the saturated C(6) ring fused to it adopts a chair conformation. In the crystal, inversion dimers linked by pairs of N—H⋯O hydrogen bonds generate R (2) (2)(8) loops.